Lipid from microalgae isolated from Cengklik Reservoir, Boyolali, Central Java for prospective biodiesel sources - Sari, Siti Lusi Arum; Suratman, Suratman; Sunarto, Sunarto; Purwoko, Tjahjadi; Larasati, Dewi; Herina, Stefanus Junliem Nugratama (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
The availability and sustainability of the algae-based biodiesel industry depend on the adequate selection of microalgae strains. Based on this, it is important to explore local microalgae from Indonesia as a feedstock for biodiesel. This study aimed to isolate and screen freshwater microalgae with lipid-producing abilities. A total of three microalgal isolates have been successfully isolated from the Cengklik Reservoir (-7.506712, 110.723582). Based on the cell morphology, the three isolates were identified as Chlorella sp., Scenedesmus sp., and Oscillatoria sp. Nile red staining indicated that the three microalgal isolates contained neutral lipid droplets in their cells, as shown by the presence of a yellow or orange luminescence under a fluorescence microscope. The results of this study indicated that Scenedesmus sp. and Oscillatoria sp. had more potential as feedstocks for biofuels due to their higher lipid content and productivity. This research succeeded in obtaining microalgae isolates from Cengklik reservoir, Boyolali, Central Java which can be used as a source of lipids for biodiesel.